DSP-based System for 2D Wideband Acoustic Source Localization using UCA-ESPRIT - Zhonglei Zou (2012)
Direction-of-arrival (DOA) estimation of the incoming signals is a basic and important technique in microphone array processing. It is applied not only for wireless communication but also for audio/speech processing systems.